2013
DOI: 10.1111/pce.12214
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of root hydraulic conductivity by methyl jasmonate and the role of calcium and abscisic acid in this process

Abstract: The role of jasmonic acid in the induction of stomatal closure is well known. However, its role in regulating root hydraulic conductivity (L) has not yet been explored. The objectives of the present research were to evaluate how JA regulates L and how calcium and abscisic acid (ABA) could be involved in such regulation. We found that exogenous methyl jasmonate (MeJA) increased L of Phaseolus vulgaris, Solanum lycopersicum and Arabidopsis thaliana roots. Tomato plants defective in JA biosynthesis had lower valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 102 publications
(250 reference statements)
2
55
0
3
Order By: Relevance
“…An antibody against phosphorylated PIP2 at the C-terminal end of PvPIP2;1 (CAIKALG{pSER}FRSNA) was also used. A previous check for the specificity of each antibody (Sanchez-Romera et al 2014) showed that each antibody was very specific to its target protein, phosphorylated or not. These antibodies were developed in rat (anti-PIP1) and in rabbits (anti-PIP2 and antiphosphorylated PIP2) by Abyntek Company (Bilbao, Spain).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…An antibody against phosphorylated PIP2 at the C-terminal end of PvPIP2;1 (CAIKALG{pSER}FRSNA) was also used. A previous check for the specificity of each antibody (Sanchez-Romera et al 2014) showed that each antibody was very specific to its target protein, phosphorylated or not. These antibodies were developed in rat (anti-PIP1) and in rabbits (anti-PIP2 and antiphosphorylated PIP2) by Abyntek Company (Bilbao, Spain).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…The interest of using this methodology is that the regulation of cell to cell water transport involves the activity of PIPs (Maurel et al, 2008), which was also evaluated in our experiments. Previous studies showed the good concordance between Lp r measured by the free exudation method and that measured by the pressure chamber method (Sánchez-Romera et al, 2014). Plant shoots were excised in their growing hydroponic medium.…”
Section: Measurement Of Lp R In the Absence Of Hydrostatic Pressure Gmentioning
confidence: 99%
“…6). Numerous studies have shown the relevant role of root ABA in regulating Lp r (Hose et al, 2000;Thompson et al, 2007;Tardieu et al, 2010;Sánchez-Romera et al, 2014) and the expression of genes encoding some families of PIP proteins as well (Beaudette et al, 2007;Mahdieh and Mostajeran, 2009). Assuming the limitations linked to all pharmacological approaches because of the possibility of side effects of inhibitors and precursors on unwanted biochemical pathways ("Materials and Methods"), our experiments indicated that the SHA-mediated increase in Lp r is ABA dependent, because the application of Fld, a specific inhibitor of ABA biosynthesis in root and shoot, abolished SHA action on Lp r .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, exogenous treatment with jasmonates increased ABA levels in different Species both under control conditions or exposed to drought. 10,11 The reciprocal treatment with exogenous ABA had no significant effect on endogenous JA levels in citrus plants. 11 In order to understand the effect of JA on plant responses to desiccation, proline accumulation after dehydration was analyzed in different Arabidopsis seedlings: a line defective in JA-Ile biosynthesis (jar1-1), 2 JA insensitive lines (jai1 and coi1-16), and an ABA insensitive line (abi2).…”
mentioning
confidence: 99%